2014
DOI: 10.14411/eje.2014.030
|View full text |Cite
|
Sign up to set email alerts
|

Does the prediction of the time of egg hatch of Thaumetopoea processionea (Lepidoptera: Notodontidae) using a frost day/temperature sum model provide evidence of an increasing temporal mismatch between the time of egg hatch and that of budburst of Quercus robur due to recent global warming?

Abstract: Abstract. Thaumetopoea processionea is a serious defoliator of oak and of medical concern whose abundance has consistently increased throughout Europe during the past two decades. This study validates a previously published frost day/temperature sum model for predicting time of egg hatch of this species using five years of recent field data from South-West Germany. This model proved satisfactory for predicting the time of egg hatch of T. processionea. Hence, the model was used to retrospectively predict the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The climate change alters the spreading of insect species, which may induce damage by feeding and/or by transmitting plant pathogens. For example, several studies have reported the recent invasion of Mediterranean plant pests like Thaumetopoea processionea in Northern European countries, including England, Denmark, and Sweden (Wagenhoff et al, 2014). Moreover, there are many regulatory restrictions on the use of conventional pesticides because of potential ecological and environmental hazard upon application (Robin and Marchand, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The climate change alters the spreading of insect species, which may induce damage by feeding and/or by transmitting plant pathogens. For example, several studies have reported the recent invasion of Mediterranean plant pests like Thaumetopoea processionea in Northern European countries, including England, Denmark, and Sweden (Wagenhoff et al, 2014). Moreover, there are many regulatory restrictions on the use of conventional pesticides because of potential ecological and environmental hazard upon application (Robin and Marchand, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The summation of these different effects can have a signifi cant effect on population fl uctuations, outbreaks and damage by forest insects (Mattson & Haack, 1987;Leskó et al, 1995Leskó et al, , 1998Csóka, 1997;Rouault et al, 2006;Dobbertin et al, 2007;Jactel et al, 2012;Klapwijk et al, 2013;Hlásny et al, 2015). the population fl uctuations, as already suggested in several earlier papers (Klapwijk et al, 2013;Wagenhoff & Veit, 2011;Wagenhoff et al, 2013Wagenhoff et al, , 2014. We assume that high spring temperatures have positive effects on the populations as under these conditions development is faster and mortality lower.…”
Section: Introductionmentioning
confidence: 77%
“…Therefore, we excluded it, although several papers (Wagenhoff & Veit, 2011;Meurisse et al, 2012;Klapwijk et al, 2013) mention that early spring (March and April) temperatures may infl uence populations due to their direct effect on larval survival and in disrupting the synchrony between budburst and egg hatch. However, the effect of this desynchronization is quite plastic, since young larvae may survive 2-3 weeks of starvation (Wagenhoff et al, 2013) and bud burst occurs earlier following mild winters and in warm early springs (Wagenhoff et al, 2014). The positive effect of temperature in the main larval feeding period is likely to be due to faster development shortening their exposure to both abiotic (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The climate change alters the spreading of insect species, which may induce damage by feeding and/or by transmitting plant pathogens. For example, several studies have reported the recent invasion of Mediterranean plant pests like Thaumetopoea processionea in Northern European countries, including England, Denmark, and Sweden (Wagenhoff et al, 2014). Moreover, there are many regulatory restrictions on the use of conventional pesticides because of potential ecological and environmental hazard upon application (Robin and Marchand, 2019).…”
Section: Introductionmentioning
confidence: 99%